Analisis Kelayakan Usaha dan Strategis Pengembangan Usaha Penyulingan Minyak Nilam - Taslim Taslim; Musaddar Musaddar; La Nalefo (Fakultas Pertanian Universitas Halu Oleo, 2022)
Business Feasibility Analysis and Business Development Strategy for Oil Patchouli Refining (Case Study Pak Safaruhin' Distillery in Langku-Langku Villa, Tiworo Tengah District, Muna Barat Regency). Under the leadership of Mr. Musaddar, S.P., M.P. my counselor and Dr Ir. La Nalefo, M.S. as a matron, ii.This study aims to determine the business productivity and development strategy of owner Safaruhin patchouli oil polishing business in Langku-Langku Villa, Tiworo Tengah District, Muna Regency West. This research was published in September 2021. The object of this research was Mr. Safaruhin as a business owner and as many as 29 farmers who participated in the success of patchouli oil polishing. The results of this study indicate that (1) Mr. Safaruhin's oil patchouli refining business could be clarified, because it has a B/C value of 1.14, (2), and there are 4 plans that can be developed by Mr. Safaruhin's patchouli oil developed. included the expansion of the land share of farmers, the expansion of the nuclear plant traders, the expansion of the patchouli oil embellishment plant and the expansion of the patchouli oil market.